Environmental Issues in Thyroid Diseases - Ferrari, Silvia Martina; Fallahi, Poupak; Antonelli, Alessandro; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
Environmental factors are determinant for the appearance of autoimmune thyroid diseases (AITD) in susceptible subjects. Increased iodine intake, selenium and vitamin D deficiency, exposure to radiation, from nuclear fallout or due to medical radiation, are environmental factors increasing AITD. Cigarette smoking is associated with Graves’ disease and Graves’ ophthalmopathy, while it decreases the risk of hypothyroidism and thyroid autoimmunity. Viral infections are important environmental factors in the pathogenesis of AITD, too, particularly human parvovirus B19 (EVB19) and hepatitis C virus. Among the many chemical contaminants, halogenated organochlorines and pesticides variably disrupt thyroid function. Polychlorinated biphenyls and their metabolites and polybrominated diethyl ethers bind to thyroid transport proteins, such as transthyretin, displace thyroxine, and disrupt thyroid function. Among drugs, interferons and iodine containing drugs have been associated with AITD. Moreover intestinal dysbiosis causes autoimmune thyroiditis. To reduce the risk to populations but also in each patient, it is necessary to comprehend the association between environmental agents and thyroid dysfunction.